If I am to be remembered : the life and work of Julian Huxley with selected correspondence - Dronamraju, Krishna R (Word Scientific, 1993)
Includes bibliographical references (p. 287-290) and index.; Sir Julian Huxley was especially noted for his versatility ? great biologist, first Director-General of UNESCO, Director of the London Zoo, bird watcher, skilled popular writer of science and a tireless champion of wildlife conservation. This book is a biographical account of Huxley as revealed through his own correspondence and the correspondence of his great contemporaries. An introductory biographical summary is followed by his and others' letters and a collection of some of his writings. A complete bibliography of Huxley is included. The book would be of great interest to all biologists, students of the United Nations, historians of science and nature conservationists.